Sosialisasi Kegiatan PPKM ( Pemberlakuan Kegiatan Pembatasan Masyarakat ) Ditingkat Desa Bersama Pemuda Karang Taruna - Donny Setiawan; Galih Farhanto; Puji Setyaningsih (Fakultas Teknik, Universitas PGRI Banyuwangi, 2021)
Until now the development of Covid-19 in Indonesia is still increasing in number. Due to the increase in Covid-19 cases, the government implemented various policies in the form of PSBB, lockdown, restrictions on a limited scale, social distancing, new normal, obeying health protocols, and other policies. The effectiveness of the PSBB in practice in the field will only be successful if every member of the community is willing to do so. Since the implementation of the Micro PPKM policy on February 9, 2021, active cases of COVID-19 have begun to be suppressed. In Gondosari Hamlet, Tamansari Village, the handling that has been carried out by the Village Government (Pemdes) and RT / RW is only limited to spraying disinfectants, starting from 1 week 1x, 1 month 1x, and currently 3 months 1x, socialization using loudspeakers regarding prevention the dangers of Covid-19. The method of activity used is the online and offline method which will be carried out by lecturers and students and students together with village youth organizations. Service activities in the form of Socialization of PPKM Activities (Enforcement of Community Restriction Activities) at the Village Level Together with Karang Taruna Youth in the form of providing education through leaflets and posters media are also accompanied by donations in the form of 100 masks, Service activities are part of efforts to increase public knowledge in terms of policy delivery and the Government's message regarding restrictions on activities in the community through PPKM, as well as about the dangers of covid-19 and prevention efforts that can be done, as well as providing masks to the community in the hope of increasing public awareness and as one of the steps to minimize the transmission of covid-19.